Biophysical and Socioeconomic Geodatabase for Land Productivity Dynamic Assessment in Ethiopia - Tibebe, Degefie; Tamene, Lulseged D. (International Center for Tropical Agriculture, 2016)
The purpose of this work is to collect, organize and develop geodatabase of spatial and non spatial data which are relevant to monitor land degradation and assess the major drivers to land degradation in Ethiopia. Accordingly, important time series biophysical (climate, vegetation, hydrology, soil...etc) and socioeconomic data (human population/demography, livestock population, major crops production and productivity....etc) are collected. Geodatabase is developed to facilitate integration and standardization of the collected data and making it suitable to use for further study. The next phase of this work is to find out the cause of land degradation in Ethiopia as human induced or (e.g. poor land management), climate driven (e.g. El Niño induced drought), or a combination of both factors at different spatial and temporal scales. Thus it is possible to devise suitable solutions to sites specific and time dependent problems